PENGARUH SIKAP DAN MOTIVASI TERHADAP MINAT BERWIRAUSAHA SISWA - Asep Munawar; Nono Supriatna (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2018)
This study aims to examine the influence of attitudes and motivation on student entrepreneurship interests, research methods used survey with quantitative approach, using a sample of 60 students of SMAN 3 Purwakarta. Data analysis technique used is Factor Analysis, Multiple Regression Analysis, and One Way Anova. The result of the research shows that the attitude has a significant effect on the entrepreneurship interest of the students, or has a significant role to the establishment of entrepreneurship interest in the students, and the motivation has a significant effect on the entrepreneurship interest of the student or has a role to the student entrepreneur interest. motivation has a significant effect on student entrepreneur interest. This shows that attitudes and motivations will provide an indirect experience to a person to have an entrepreneurial interest, because at least a person or a student has the knowledge of how to run a business, how to deal with problems in a business, how to market a product or service, how to access capital and etc.